Development and validation of a score for the screening of Loei urolithiasis patients - Santanapipatkul, Krit; Jantakun, Wilairak (Insight Urology, 2022)
Objective: To evaluate risk factors associated with stone formation and development and validation of a score for screening Loei urolithiasis patients. Materials and Methods: This cross-sectional study included 1008 individuals, 466 of which were urolithiasis patients and 542 non-urolithiasis, with no history of stone and no evidence of stone from investigations at Loei Hospital between July 2014 and January 2019. This group was used effectively as a control group. Questionnaires were used to collect information regarding demographic parameters, food and water intake and frequency. The information was used to identify any associations with stone formation using logistic regression analysis. Univariable and multivariable analysis were carried out in order to build a predictive model for the likelihood of stone formation. The strength of the classifier from the predictive model was evaluated using the area under the receiver operating characteristics (ROC) curve. Results: Multivariable analysis showed increasing BMI (adjusted odds ratio (aOR) =1.06; 95% CI: 1.01-1.1, p = 0.01); male gender (aOR = 2.09; 95%CI: 1.46-2.98, p < 0.001); family history of urolithiasis (a OR = 2.81; 95% CI: 1.78-4.42, p < 0.001); farmer (aOR = 3.59; 95% CI: 2.44-5.29, p < 0.001); working time > 8 hours/day (aOR = 2.19; 95%CI: 1.47-3.27, p < 0.001); drinking more than 2 liters per day of water (aOR = 1.58; 95%CI: 1.13-2.22, p = 0.01); always eat water spinach (aOR = 3.37; 95% CI: 1.47-7.74, p = 0.01); always eat bamboo shoots (aOR = 9.53; 95% CI: 4.54-19.99, p < 0.001); eat Laab/Koi (a local Thai spicy salad made of raw meat and fish) more than or equal to 3 times per week (aOR = 1.75; 95% CI: 1.05-2.9, p = 0.03) and drink bottled water (aOR = 0.17.; 95% CI: 0.12-0.24, p < 0.001) were statistically significant for stone formation. The predictive model for the likelihood of stone formation has a cut-off value greater than or equal to 0.46 for a sensitivity of 72.41%, a specificity of 79.52%, and area under the ROC curve of 0.83. Conclusions: Increasing BMI, being of male gender, a family history of urolithiasis, farmers, working time > 8 hours/day, regular consumption of water spinach, regular consumption of bamboo shoots, eat Laab/Koi more than or equal to 3 times per week were associated significantly with stone formation. We developed and validated a predictive model to indicate the likelihood of stone formation, which can be utilized for the screening of Loei urolithiasis patients facilitating early detection and early treatment.